Karakteristik Kepemimpinan Spiritual Kiai - Murtaufiq, Sudarto; Imaduddin Ahmad, Victor (MADINAH, 2019)
The spiritual leadership of the kiai (cleric) can at least be characterized through three characteristics that are related to one another, namely iman, Islam and Ihsan. Different from conventional leadership, the characteristics of the kiai's spiritual leadership certainly emphasize these three dimensions as a form of fulfillment of spiritual vision dealing with self-servitude to Allah SWT. While the material and technical dimensions are more complementary. So, as far as the spiritual dimension is the main factor in an organizational or social system, the spiritual leadership of the kiai has a theological, philosophical, psychological and sociological reasons.